2004
DOI: 10.1111/j.1478-9299.2004.00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Stalinism as a Civilization: New Perspectives on Communist Regimes

Abstract: A new line of inquiry into the history of communist regimes and the cold war has emerged. Pioneered by Stephen Kotkin and other American historians, it views Stalinism as the defining era of socialism, building a specific anti-capitalist and illiberal modernity that mustered voluntary participation and international legitimacy. This model of Stalinism as a rival civilization, held together by participatory totalitarianism, challenges older research on communist regimes -both revisionist and totalitarian studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…On the other hand, the idea that communist regimes had invented a novel and superior type of representative system goes back at least to the 1930s (cf. Hedin, 2004;Webb & Webb, 1936, pp. 13-15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the idea that communist regimes had invented a novel and superior type of representative system goes back at least to the 1930s (cf. Hedin, 2004;Webb & Webb, 1936, pp. 13-15).…”
Section: Discussionmentioning
confidence: 99%
“…The present study, of East-West policy isomorphism in Europe during the Cold War, highlights the complex role of communist regimes as competing, illiberal modernities in this process (cf. Hedin, 2004).…”
Section: Historical Global Neo-institutionalismmentioning
confidence: 99%
“…Although the ideological struggle in post-Cold War international relations has been weakened, it does not mean that Western diplomacy has been rid of the influence of ideological factors but has a new focus on the object. The current ideological struggle is not only a struggle between communism and capitalism but even a struggle between different "civilizations" (Hedin 2004). After the Soviet and Eastern socialist systems disintegrated, the western powers in the ideological offensive were more prosperous.…”
Section: Case Study: Situation In Afghanistanmentioning
confidence: 99%
“…Scott’s assumption of pervasive resistance is akin to 1980s revisionist research on communist regimes, which depicted citizens as persevering, tenacious liberal subjects, with the minds of a Westerner, unencumbered by their historical context, who made rational, selfish business deals with the communist regimes for their own individual advantage (Krylova, 2003). In contrast, post-1991 research has shown how many citizens took communist ideology seriously and held a genuine belief in the hostile and dangerous nature of the capitalist West – as propagated by the communist regimes (Kotkin, 1995; Hedin, 2004). Many ordinary people – not to speak of the elite at the universities – experienced a sense of positive self-integration under communist regimes, and were faithful and loyal participants in the state-led internationalist project to build a socialist world (Hellbeck, 2003; Sabrow, 2001).…”
Section: The Micro-level Mechanismsmentioning
confidence: 99%
“…Notably however, in congruence with recent interpretations of the concept of totalitarianism, communist regime travel cadre systems were not simply coercive, but organised to foment and harness willing discursive participation, active initiative and sincere belief (cf. Hedin, 2004). In this sense, the system was not only despotic, but enabling; an infrastructural capacity to seed out, educate, mobilise and direct loyal regime sympathisers in the everyday participatory service of the state (cf.…”
Section: Travel Cadre Systems As Totalitarian State Capacitymentioning
confidence: 99%